OPTIMALISASI JUMLAH PERJALANAN KRL LINTAS JAKARTA KOTA- BOGOR TERHADAP DEMAND PENUMPANG MENGGUNAKAN ARIMA BOX-JENKINS - ARINDA LELIANA; Shalsabila Diast Ferlianne; Muhardjito Muhardjito (LPPM, 2023)
The large number of people's interest in using the KRL has caused the demand for KRL travel needs to continue to increase. The Jakarta Kota-Bogor route is quite a busy KRL line because this route is included in the busiest route category with a maximum journey of 15 minutes per day. The large number of people's interest in using the KRL has caused the demand for KRL travel needs to also continue to increase. So that a study is needed related to optimizing the calculation of the number of trips needed based on passenger demand by taking into account the available traffic capacity and headway. The ARIMA method is applied to find out the number of passengers in the next 5 years whether it goes up or down. Furthermore, the calculation of the headway and traffic capacity is used as a consideration in determining the number of trips needed. From the calculation results, there is an increase in the number of passengers from 2022 to 2026 of 0.83% with the availability of 134 trips and a headway of 2-4 minutes. The number of trips required during 2022 is 134 trips, 140 trips in 2023, 144 trips in 2024, 145 trips in 2025 and 2026 with a total of 146 trips. An additional 30 trips are needed in 2022, an additional 36 trips are needed in 2023, an additional 40 trips are needed in 2024, an additional 41 trips are needed in 2025, and an additional 42 trips are needed in 2026. With the number of formations for each series of 12 trainsets and a total transport capacity of 1,800 people.